Regularized Mixed Variational-Like Inequalities - Muhammad Aslam Noor; Khalida Inayat Noor; Saira Zainab; Eisa Al-Said (Journal of Applied Mathematics)
We use auxiliary principle technique coupled with iterative regularization method to suggest and analyze some new iterative methods for solving mixed variational-like inequalities. The convergence analysis of these new iterative schemes is considered under some suitable conditions. Some special cases are also discussed. Our method of proofs is very simple as compared with other methods. Our results represent a significant refinement of the previously known results.